The Relation Between Islamic Business Ethics and The Performance of Traders in The Traditional Market of Cipanas - Deni Lubis; Siti Maryam; Qoriatul Hasanah (Business Economic, Communication, and Social Sciences Journal (BECOSS), 2023)
Cipanas market is the first SNI-certified market in Cianjur, which has the slogan Gerbang Marhamah (Gerakan Pembangunan Masyarakat Berakhlakul Karimah) and the majority of the traders are Muslim. This study aims to analyze the application of Islamic business ethics to the business success of traders in Cipanas Market with a sample of 90 food and food traders. Data were analyzed using Partial Least Square-Structural Equation Modeling (SEM-PLS) and descriptive analysis. The results of data analysis show that management ethics, marketing ethics, and environmental ethics have a positive effect on business success and business blessings have a positive effect on financial improvement, customer growth, and employee loyalty. Overall, the application of Islamic business ethics has a positive effect on the business success of Cipanas market traders. Local government are expected to monitor trading practices in the Cipanas market, such as the accuracy of scales and price games so that sellers maintain ethics in their business.